A Brief Overview of the History of Sea Resorts Along the Baltic Coast - Plessen, Marie-Louise Von (Recent Research Advances in Arts and Social Studies Vol. 4, 2024)
The history of sea-resorts along the Baltic Sea over the last three centuries is an almost unknown topic of European integration in terms of (social) hygiene, investment, culture, architecture as well as the important contribution of Jewish origin and the impact of British influence, due to dynastic networks. This chapter aims to highlights the History of Sea Resorts along the Baltic Coast.